64.2k views
4 votes
Simplify 5(a+6)−a+7a−18

2 Answers

2 votes

Answer: 11a+12

Explanation:

User Rajeesh Madambat
by
5.0k points
7 votes

Answer:

11a + 12

Explanation:

For this problem, we will simply use the distributive property both forwards to gather all of the like terms, and then backward to simplify the like terms.

5 ( a + 6 ) - a + 7a - 18

= 5a + 30 - a + 7a - 18

= 5a - a + 7a + 30 - 18

= a ( 5 + -1 + 7 ) + 30 - 18

= a ( 4 + 7 ) + 12

= a ( 11 ) + 12

= 11a + 12

Hence, the simplification for 5(a+6)-a+7a-18 is 11a + 12.

Cheers.

User Sajmir
by
5.0k points